Determinants of Emergency Department Length of Stay Using the Time Frame Emergency Care Model: A Retrospective Study - Sompie, Lydia Maryendi; Lestari, Retno; Suryanto, Suryanto (Journal of Applied Nursing and Health, 2025)
Background: Timely management in the emergency department (ED) is critical for patient safety and quality of care. Prolonged Length of Stay (LOS) in the ED, often linked to delays in patient processing, can lead to poor outcomes, particularly in high-risk populations. This study aims to explore the time-related factors influencing LOS using the Time Range Guidance Model. Methods: A retrospective cross-sectional study was conducted, analysing 377 patient records from June to August 2025. Data were extracted from electronic medical records (EMR), focusing on time intervals for initial assessment, review/consultation, and transfer phases. Multivariate regression was used to identify the factors influencing LOS. Results: The review/consultation time (β = 0.3, p < 0.001) and transfer waiting time (β = 0.356, p < 0.001) were significant predictors of LOS. The model explained 22.6% of the variability in LOS (Adjusted R² = 0.226). Initial assessment time did not significantly correlate with LOS (r = 0.045, p = 0.321). Conclusion: Delays in the review/consultation and transfer phases have a greater impact on ED LOS than the initial assessment. These findings suggest that optimizing these phases can improve ED efficiency and patient outcomes, particularly in resource-constrained settings such as Indonesia.